(untitled) (Research, Society and Development, 2021)
Aim: To verify the adherence to hand hygiene by healthcare workers in the fight against the COVID-19 pandemic. Methodology: Articles found in PubMed/MEDLINE, SCOPUS and Cochrane Library databases were reviewed. The following inclusion criteria were defined: cross-sectional studies carried out through observation or questionnaire that evaluated the adherence of health professionals to hand hygiene during the COVID-19 pandemic, published from January 2020 to May 2021. After the searches, the articles selected by the abstracts were read in full. Studies that did not specify the period in which they were carried out were excluded. Results: 331 articles were found, however only 23 were included in the literature review, showing that the most prevalent observation was in relation to exposure or time of hand hygiene, evaluated in 11 studies. Conclusion: The rate of adherence to hand hygiene in the pandemic was significantly higher compared to the pre-COVID-19 period. Doctors and nurses are the professionals who most frequently clean their hands during the pandemic, especially after contact with patients. The technicians and nursing assistants, on the other hand, were less adept. The frequency of cleaning was higher in SARS-CoV-2 transmission peaks.